The real relationship: the Portuguese version of the Real Relationship Inventory-Client form - Pedro Rodrigues Ribeiro; David Dias Neto (Research in Psychotherapy, 2023)
The Real Relationship is a relational construct that has influenced other constructs, like the working alliance, although empirically neglected. The development of the Real Relationship Inventory provides a reliable and valid way of measuring the Real Relationship in research and clinical applications. This study aimed to validate and explore the psychometric properties of the Real Relationship Inventory Client Form with a Portuguese adult sample in the context of psychotherapy. The sample includes 373 clients currently in psychotherapy or concluded recently. All clients completed the Real Relationship Inventory (RRI-C) and the Working Alliance Inventory. The confirmatory analysis revealed the same two factors in the RRI-C for the Portuguese adult population, Genuineness and Realism. The observation of the same factor structure suggests the cross-cultural value of the Real Relationship. The measure demonstrated good internal consistency and acceptable adjustment. A significant correlation was found between the RRI-C and the Working Alliance Inventory and significant correlations between the Bond and Genuineness and Realism subscales. The present study reflects on the RRI-C while also contributing to the importance of the Real Relationship in different cultures and clinical contexts.